The Human Organism is a Biophysical–Biopsychological System - Vincze, Janos; Vincze-Tiszay, Gabriella (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Healthy and ill people both try to achieve the required performance and satisfaction of this, but they experience differently their activities accompanied by secondary feelings, their critical attitude and their compliance with social desires. Exceeding these correspondences requires the operation of countermeasures in all people, which at times are barely noticeable because they are embedded in the personality structure or alternately use the entire arsenal of mechanisms. If a biopsychological system responds specifically to an external stimulus, it means that the value of some of its parameters changes and then returns to its original state of homeostasis when the response is complete. Parameters characterized by static equilibrium and is involved in the response return their values over time to their original value such that its envelope is an exponential (ascending or descending) curve. The parameter that is characterized by a state of dynamic equilibrium and is involved in the response returns to its original value with attenuated harmonic oscillation after its completion. The duration of the return is different for each parameter, and the normal state of homeostasis is determined by the parameter with the slowest finish.